Effect of Olive Kernel thermal treatment (torrefaction vs. slow pyrolysis) on the physicochemical characteristics and the CO2 or H2O gasification performance of as-prepared biochars. (18th August 2021) - Lampropoulos, Athanasios; Kaklidis, Nikolaos; Athanasiou, Costas; Montes-Morán, Miguel A.; Arenillas, Ana; Menéndez, J. Angel; Binas, Vassilios D.; Konsolakis, Michalis; Marnellos, George E.
Abstract: The thermochemical conversion of biomass through its gasification has been widely explored during the last decades. The generated bio-syngas mixture can be directly used as fuel in thermal engines and fuel cells or as intermediate building block to produce synthetic liquid fuels and/or value added chemicals at large scales. In the present work, the effect of Greek olive kernel (OK) thermal treatment (torrefaction at 300 °C vs. slow pyrolysis at 500 and 800 °C) on the physicochemical characteristics and CO2 or H2 O gasification performance of as-produced biochars is examined. Both the pristine OK sample and biochars (OK300, OK500, OK800) were fully characterized by employing a variety of physicochemical methods. The results clearly revealed the beneficial effect of thermal pretreatment on the gasification performance of as-prepared biochars. Α close relationship between the physicochemical properties of fuel samples and gas production was disclosed. Carbon dioxide gasification leads mainly to CO with minor amounts of H2 and CH4, whereas steam gasification results in a mixture containing CO2, CO, H2 and CH4 with a H2 /CO ratio varied between 1.3 and 2.3. The optimum gasification performance was obtained for the slowly pyrolyzed samples (OK500 and OK800), due to their higher carbon and ash content as well as to their higher porosity and less ordered structure compared to pristine (OK) and torrefied (OK300) samples. Highlights: CO2 and H2 O gasification of olive kernel and its torrefied and pyrolyzed chars was examined. Chars with less ordered structures, increased C, ash content and higher porosity were obtained. Regardless the gasification agent, an increase on gas production was observed with treatment temperature. A close relationship between the gasification performance and the physicochemical properties was revealed. The optimum behavior in terms of gas production was obtained for chars pyrolyzed at 500 and 800 °C.